2015
DOI: 10.1074/jbc.m115.691493
|View full text |Cite
|
Sign up to set email alerts
|

The Voltage-dependent Anion Channel 1 Mediates Amyloid β Toxicity and Represents a Potential Target for Alzheimer Disease Therapy

Abstract: The voltage-dependent anion channel 1 (VDAC1), found in the mitochondrial outer membrane, forms the main interface between mitochondrial and cellular metabolisms, mediates the passage of a variety of molecules across the mitochondrial outer membrane, and is central to mitochondria-mediated apoptosis. VDAC1 is overexpressed in post-mortem brains of Alzheimer disease (AD) patients. The development and progress of AD are associated with mitochondrial dysfunction resulting from the cytotoxic effects of accumulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(108 citation statements)
references
References 72 publications
4
95
0
1
Order By: Relevance
“…These include intracellular communication, as mediating calcium signal between the ER and mitochondria ( 41 ), being part of the outwardly rectifying depolarization-induced chloride (ORDIC) channel complex ( 42 ), regulate cell volume in brain ( 43 ), and mediate ATP release ( 44 ). Interestingly, silencing VDAC1 expression by specific small interfering RNA (siRNA) was shown to prevent the entry of amyloid beta (Aβ) into the cytosol, as well as Aβ-induced toxicity ( 45 ), suggesting the involvement of pl-VDAC1 in Aβ cell entry and in inducing mitochondrial dysfunction and apoptosis ( 46 ). These and other proposed functions for plVDAC were recently presented and discussed ( 31 ).…”
Section: Voltage-dependent Anion Channel (Vdac) Isoforms Structure mentioning
confidence: 99%
See 1 more Smart Citation
“…These include intracellular communication, as mediating calcium signal between the ER and mitochondria ( 41 ), being part of the outwardly rectifying depolarization-induced chloride (ORDIC) channel complex ( 42 ), regulate cell volume in brain ( 43 ), and mediate ATP release ( 44 ). Interestingly, silencing VDAC1 expression by specific small interfering RNA (siRNA) was shown to prevent the entry of amyloid beta (Aβ) into the cytosol, as well as Aβ-induced toxicity ( 45 ), suggesting the involvement of pl-VDAC1 in Aβ cell entry and in inducing mitochondrial dysfunction and apoptosis ( 46 ). These and other proposed functions for plVDAC were recently presented and discussed ( 31 ).…”
Section: Voltage-dependent Anion Channel (Vdac) Isoforms Structure mentioning
confidence: 99%
“…High-levels of VDAC1 were demonstrated in the dystrophic neurites of Aβ deposits in AD post-mortem brains and amyloid precursor protein transgenic mice ( 300 ). VDAC1 was shown to participate in Aβ-induced toxicity ( 45 , 301 , 302 ) where Aβ–VDAC1 interactions are toxic to AD-affected neurons ( 303 ) and VDAC1 interactions with Aβ and phosphorylated Tau lead to mitochondrial dysfunction ( 302 ). Recently ( 45 ), we demonstrated that Aβ interacts directly with VDAC1, specifically with the N-terminal region.…”
Section: Vdac Involvement In Diseases Other Than Cancermentioning
confidence: 99%
“…In the present study, we investigated role of miR‐320a in regulating ATP release from astrocytes via the control of voltage dependent anion channel 1 (VDAC1) that culminates into astroglia‐induced neuronal death. VDAC1 has been implicated in various neurological disorders like Alzheimer's disease, Down Syndrome, Amyotrophic Lateral Sclerosis and Parkinson's Disease (Chu et al, ; Israelson et al, ; Smilansky et al, ; Yoo et al, ). VDAC1 is the most abundant outer membrane mitochondrial protein and provides major channel gateway for ATP release from mitochondria (Rostovtseva and Colombini, ).…”
Section: Introductionmentioning
confidence: 99%
“…Esta interacción resulta en la formación de un hetero-oligomero de pl-VDAC-1-Aβ, permitiendo Aβ entrar a la célula. Aβ citosólico interactúa con VDAC-1 mitocondrial en el dominio N-Ter permitiendo su subsecuente oligomerización, y consecuente liberación de Citocromo c y finalmente muerte celular apoptótica (26).…”
Section: Figuraunclassified